Orientational ordering in molecular crystals - Harris, A.B. (Физика низких температур, 1996)
The general phenomenon of orientational ordering in molecular crystals is reviewed. Some of the basic physical questions which arise in connection with orientational ordering in molecular crystals are enumerated and experimental techniques used to address them are described. The description of orientational ordering in terms of order parameters and the resulting form of the Landau expansion is discussed for several typical cases. The relation to the modern theory of critical phenomena and notions of elementary excitations are also discussed. Analogous theories of dynamics are briefly mentioned.